RUSSIAN IS THE RICHEST LANGUAGE IN THE WORLD - Elmurodova Mohichehra Kamoliddin kizi; Sattorova Saodat; Abduazizova Shakhzoda; Raupova Rohatoy (International Engineering Journal For Research & Development, 2021)
The richness of any language is largely determined by the richness of the dictionary. Russian is very complex, but that doesn’t make it very attractive. Many writers say that in Russian you can recognize any conversation, contact with the enemy, friendly conversation, because it can better convey all the feelings and emotions than in other languages.